The Emerald Handbook on Cryptoassets Investment Opportunities and Challenges. - Baker, H. Kent (Emerald Publishing Limited, 2023)
Bitcoin's introduction as the first cryptoasset in 2009 ushered in a new era, generating much interest, excitement, and growth. A cryptoasset is a digital asset using blockchain technology to regulate the generation of new units and verify and secure transactions.